Out of body experiencies : how to have them and what to expect - Peterson, Robert (Charlottesville, Va : Hampton Roads Publishing Co., 1997)
This text teaches the reader not only how to get in and out of body, but also how to deal with fear, how to see and navigate, where to venture and what to encounter